Moana (Disney Movie Collection: A Special Disney Storybook Series, 2015)
Moana is destined to follow in her father's footsteps and take over as chief of Motunui one day. But when danger threatens her island she sets sail on an adventure to save her people. Will Moana be able to unlock the mystery of the sea and discover her true destiny? Enjoy this exclusive large-size Disney movie storybook, featuring beautifully illustrated pages fans can treasure for years to come.